Effectiveness of Ascophyllum nodosum and Fucus vesiculosus on Metabolic Syndrome Components: A Real-World, Observational Study - Antonio Nicolucci; Maria Chiara Rossi; Massimiliano Petrelli (Journal of Diabetes Research)
Introduction. Gdue is a nutraceutical obtained from the association of two marine algae, Ascophyllum nodosum and Fucus vesiculosus, in addition to chromium picolinate, which could be useful for the treatment of dysglycemia, overweight, and the other components of the metabolic syndrome. The aim of the study was to assess the real-world effectiveness and safety of Gdue when administered to subjects with one or more components of the metabolic syndrome. Methods. A longitudinal, retrospective, observational study, conducted among primary care physicians, nutritionists, and specialists from various disciplines. The impact of 180 days of administration of Gdue was assessed on body weight, waist circumference, fasting blood glucose, HbA1c, lipid profile, and blood pressure levels. The likelihood of experiencing a first major cardiovascular event over ten years was estimated using Italian risk charts. General linear models for repeated measures were applied to assess changes in the parameters of interest during the follow-up. Results are expressed as estimated marginal means with their 95% confidence interval. Results. Overall, 505 patients were enrolled by 282 physicians. After 6 months of treatment with Gdue, body weight was reduced on average by 7.3 kg (-8.0; -6.6), waist circumference by 7.5 cm (-8.2; -6.8), fasting blood glucose by 16.3 mg/dL (-17.8; -14.7), HbA1c by 0.55% (-0.62; -0.49), systolic and diastolic blood pressure by 7.1 mmHg (-8.3; -6.0) and 4.2 mmHg (-5.0; -3.5), respectively, LDL cholesterol by 18.2 mg/dL (-21.2; -15.3), and triglycerides by 39 mg/dL (-45; -32). HDL cholesterol was significantly increased by 2.9 mg/dL (0.7; 5.0). The 10-year risk of cardiovascular events significantly decreased by 1.8%, corresponding to a relative risk reduction of 27.7%. Conclusion. Our real-world study shows that 6 months of treatment with Gdue have an impact on all the components of the metabolic syndrome, thus offering the potential for decreasing the cardiovascular risk associated with metabolic syndrome.